Territorial development through cultural tourism and creative activities - Ludovico Solima; Antonio Minguzzi (Mondes du Tourisme, 2014)
The aim of this paper is to identify an interpretative framework for the competitiveness of tourism destinations defined by a strong tangible or intangible cultural heritage and which have identified development patterns focused around local cultural and creative industries. This paper will analyse in depth both Italian and international literature on tourist destinations with a strong cultural heritage, evaluating the implications of creative industries for regional development. The resulting model will help to develop a coordinated and comprehensive management policy for creative tourism destinations. This research aims at contributing to the literature on destination management, which, whilst extensive at an international level, is relatively scarce for in-depth studies on cultural heritage and the relationship between cultural and creative industries and local development processes. For these reasons, although the approach to this work can only be based upon marginal increases in knowledge, it aims at setting out a new and highly innovative framework. Achieving the desired results will contribute not only to the scientific debate on the subject, but also support regional development initiatives as defined by tourist destination policies.